2018
DOI: 10.1111/jce.13743
|View full text |Cite
|
Sign up to set email alerts
|

Five‐year experience with pulmonary vein isolation using the second‐generation cryoballoon for treatment of persistent atrial fibrillation

Abstract: PVI using CB-Adv in patients with persistent AF is accompanied by a learning curve and facilitates a satisfactory outcome, followed by the proper selection of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 23 publications
(62 reference statements)
3
15
0
Order By: Relevance
“…In accordance with previous findings, LA diameter, duration of AF history, and early recurrence were found to be independent predictors of late recurrence in our current study. While early recurrence, LA diameter, and duration of AF history were found as the predictors of late ATa recurrence in paroxysmal AF patients, only LA diameter was found to be associated with late recurrence in persistent AF patients of our study population, which were also consistent in very recent study findings …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with previous findings, LA diameter, duration of AF history, and early recurrence were found to be independent predictors of late recurrence in our current study. While early recurrence, LA diameter, and duration of AF history were found as the predictors of late ATa recurrence in paroxysmal AF patients, only LA diameter was found to be associated with late recurrence in persistent AF patients of our study population, which were also consistent in very recent study findings …”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, in the multicenter Italian Clinical Service 1STOP project, Tondo et al reported that the AF‐free survival was 63.9% at 12 months and 51.5% at 18 months in 486 nonparoxysmal AF patients. Furthermore, Akkaya et al reported a 67.9% ATa‐free success rate in 102 persistent AF patients with a 5‐year follow‐up. The difference in regard to success rates in such patient groups between center‐based studies most commonly depends on the study population, patient characteristics, and operator experience rather than center experience for CB ablation, and follow‐up methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Again, its value in PerAF is less well documented. Some early studies showed very low success rates in the range of 30-40%, whereas more recent trials reported efficacy exceeding 50% [2][3][4][5] . The rationale for using CB in PerAF is based on the fact that CB not only effectively isolates PV but also affects surrounding atrial tissue, and thus also modifies the substrate for AF [10] .…”
Section: Discussionmentioning
confidence: 99%
“…While the value of RF ablation in PerAF has been examined by several studies [1] the role of CB ablation in these patients is less clear. A few studies have suggested that this technique may be useful in PerAF, reaching an efficacy rate of 59-65% [2][3][4][5] . However, data are limited and come from highvolume and very experienced centres.…”
Section: Introductionmentioning
confidence: 99%
“…In an observational study of 281 patients with persistent AF, long‐term outcomes after second generation cryoballoon evaluation were examined. The 1‐year freedom from the clinical atrial arrhythmia rate was 76%, which fell over 5 years to approximately 50% . Although these rates are similar to those achieved with radiofrequency ablation catheters because the second generation cryoballoon is a more durable tool for pulmonary vein isolation, the mechanisms behind these persistently elevated arrhythmia recurrence rates need to be better understood.…”
mentioning
confidence: 88%